The Development of CounselCare: Student Mental Health Assessment for SM Stella Maris using Laravel Framework - BINTI MOHD NADZREE, NURIN BATRISYIA EMIRA; NUR ARIFFIN BIN MOHD ZIN (Applied Information Technology And Computer Science, 2024)
The rising prevalence of mental health issues among high school students necessitates innovative solutions, leading to the creation of CounselCare—a web-based system tailored for SM Stella Maris. Utilizing the Depression Anxiety Stress Scales (DASS) for crucial mental health evaluations, CounselCare features mental health assessment, results showing levels for each category (Depression, Anxiety, and Stress), assessment questions management, and case management. The system includes modules for login, assessing mental health, managing assessment questions, managing cases, managing psychologists, and managing student and counsellor accounts. Counsellors can manage students with intermediate, severe, and very severe levels by scheduling intervention appointments, allowing second assessments post-intervention, and generating psychologist referral letters for parents if high levels persist. Developed using the Prototyping Model technique, CounselCare revolutionizes mental health assessments in educational settings, emphasizing environmental sustainability and proactive mental health interventions, representing a progressive step towards addressing growing mental health concerns among high school students.